Adolescent body dissatisfaction and disordered eating: Predictors of later risky health behaviours. (October 2019) - Bornioli, Anna; Lewis-Smith, Helena; Smith, Andrew; Slater, Amy; Bray, Isabelle
Abstract: Rationale: Body dissatisfaction is prevalent among teenagers, and may influence the uptake of risky health behaviours. Objective: The study assessed the influence of body dissatisfaction on smoking, cannabis use, drug use, self-harm, gambling, and drinking and the mediating role of disordered eating in a population-based sample of British adolescents. Method: Participants were 2634 females and 1684 males from the Avon Longitudinal Study of Parents and Children (ALSPAC) cohort. Logistic regression was used to test if body dissatisfaction at 14 years old predicted the onset of risky health behaviours at 21 years old. Mediation analysis tested the mediating role of disordered eating at 16 years old on each risky health behaviour. Results: Among females, body dissatisfaction predicted smoking (OR = 1.40, 95% CI = 1.15, 1.72), cannabis use (OR = 1.20, 95% CI = 1.00, 1.43), drug use (OR = 1.51, 95% CI = 1.20, 1.90), self-harm (OR = 1.44, 95% CI = 1.13, 1.84) and high-risk drinking (OR = 1.41, 95% CI = 1.10, 1.80). Disordered eating symptoms had mediating effects on some behaviours. Among males, body dissatisfaction predicted smoking (OR = 1.44, 95% CI = 1.14, 1.81) and no effect of disordered eating was found on any risky health behaviour. Conclusions: This is the first prospective study to demonstrate that body dissatisfaction in adolescence predicts the occurrence of several risky health behaviours, and elucidates the mediating role of disordered eating. The findings highlight that body dissatisfaction is a public health concern. Early interventions to promote body satisfaction may reduce the prevalence of later risky health behaviours. Highlights: Adolescent body dissatisfaction predicts onset of risky health behaviours. Disordered eating mediated effect of body dissatisfaction on some behaviours. Body dissatisfaction should be viewed as a public health concern. Early body image interventions may reduce onset of later risky health behaviours. These patterns were most marked for females and less present for males.